Measuring Time Use of Older Couples: Lessons from the Panel Study of Income Dynamics. Issue 4 (November 2013) - Freedman, Vicki A.; Stafford, Frank; Schwarz, Norbert; Conrad, Frederick
Time diaries are a well-established method for providing population estimates of the amount of time and types of activities respondents carry out over the course of a full day. This article focuses on a computer-assisted telephone application developed to collect multiple, same-day 24-hour diaries from older couples who participated in the 2009 Panel Study of Income Dynamics (PSID). We present selected findings from developmental and field activities, highlighting methods for three diary enhancements: (1) implementation of a multiple, same-day diary design; (2) minimizing erroneous reporting of sequential activities as simultaneous; and (3) tailoring activity descriptors (or "follow-up" questions) that depend on a precoded activity value. A final section discusses limitations and implications for future time diary efforts.